De uma freguesia serra acima à costa atlântica: produção e comércio da aguardente na cidade de São Paulo (1765-1822)* - Moura, Denise Aparecida Soares De [UNESP] (Programa de Pós-Graduação em História Social da Universidade Federal do Rio de Janeiro, 2012)
This article presents the conclusions of a research about the production and trade of liquor (the Brazilian sugarcane alcohol) in rural estates of a parish of the city of São Paulo, within the context of this product's trade in the Portuguese Empire at large between 1765 and 1822. The research was based on the Maços de População da Capital, a population census for the city of São Paulo, especially the 1802 issue, and the import-export maps produced by Customs at the port of the village of Santos for the Real Junta de Comércio [Royal Chamber of Commerce] in Rio de Janeiro.

Este artigo apresenta conclusões de uma pesquisa sobre a produção da aguardente em engenhos e sítios de uma freguesia da cidade de São Paulo, dentro do panorama mais amplo do comércio desse produto no Império português entre 1765 e 1822. Para tanto foram utilizados os Maços de População da Capital, especialmente do ano de 1802, e os mapas de importação e exportação da vila de Santos produzidos por sua alfândega para a Real Junta de Comércio, no Rio de Janeiro.
Keywords: Brazilian liquor; colonial trade; sugar mill owners; rural production; colonial parishes.; aguardente; comércio colonial; senhores de engenho; produtor rural; freguesias.